Anger, agency, risk and action: a neurobehavioral model with proof-of-concept in healthy young adults - White, Tara L.; Gonsalves, Meghan A.; Zimmerman, Chloe; Joyce, Hannah; Cohen, Ronald A.; Clark, Uraina S.; Sweet, Lawrence H.; Lejuez, Carl W.; Nitenson, Adam Z. (Frontiers in Psychology, 2023)
Introduction Anger can engender action by individuals and groups. It is thus important to understand anger’s behavioral phenotypes and their underlying neural substrates. Here, we introduce a construct we term agentic anger, a negatively valenced internal state that motivates action to achieve risky goals. We evaluate our neurobehavioral model via testable hypotheses in two proof-of-concept studies. Study 1 Methods Study 1 used the Incentive Balloon Analogue Risk Task in a within-subjects, repeated measures design in 39 healthy volunteers to evaluate: (a) impact of blockade of reward on agentic anger, assessed by self-reports of negative activation (NA), (b) impact of achievement of reward on exuberance, assessed by self-reports of positive activation (PA), (c) the interrelationship of these valenced states, and (d) their relationship with personality. Study 1 Results Task-induced NA was positively correlated with task-induced PA, risk-taking on the task and trait Social Potency (SP), a measure of trait agency and reward sensitivity on the Multidimensional Personality Questionnaire Brief-Form. Study 2 Methods Study 2 assessed functional MRI response to stakes for risk-taking in healthy volunteers receiving 20 mg d-amphetamine in a double-blinded, placebo-controlled crossover design (N = 10 males), providing preliminary information on ventral striatal response to risky rewards during catecholamine activation. Study 2 Results Trait SP and task-induced PA were strongly positively related to catecholamine-facilitated BOLD response in the right nucleus accumbens, a brain region where DA prediction error signal shapes action value and selection. Participants’ task-induced NA was strongly positively related with trait SP and task-induced PA, replicating the findings of Study 1. Discussion Together these results inform the phenomenology and neurobiology of agentic anger, which recruits incentive motivational circuitry and motivates personal action in response to goals that entail risk (defined as exposure to uncertainty, obstacles, potential harm, loss and/or financial, emotional, bodily, or moral peril). Neural mechanisms of agency, anger, exuberance, and risk-taking are discussed, with implications for personal and group action, decision-making, social justice, and behavior change.